A Rod‐Packing Microporous Hydrogen‐Bonded Organic Framework for Highly Selective Separation of C2H2/CO2 at Room Temperature1. Issue 2 (13th November 2014) - Li, Peng; He, Yabing; Zhao, Yunfeng; Weng, Linhong; Wang, Hailong; Krishna, Rajamani; Wu, Hui; Zhou, Wei; O'Keeffe, Michael; Han, Yu; Chen, Banglin
Abstract Self‐assembly of a trigonal building subunit with diaminotriazines (DAT) functional groups leads to a unique rod‐packing 3D microporous hydrogen‐bonded organic framework (HOF‐3). This material shows permanent porosity and demonstrates highly selective separation of C2H2/CO2 at ambient temperature and pressure.